Geração de potência e energia elétrica a partir da gaseificação de rejeitos de biomassa - Rumão, Adriano Sitônio (2013)
The main goal of this study is the generation of electricity using a modern open top biomass gasifier, (having a water gas cleaning system) imported from India, and a 36 kVA engine-generator. The engine, originally a Diesel MWM D229-4 was converted at the Laboratório de Inovação da UFPB to run just with poor gas from the gasifier. The fact that the imported gasifier had been designed to feed a dual engine to generate at the maximum 20 kWe, caused some difficulty when associated with the converted engine which ran just with gas. Therefore, drastic changes needed to be introduced at the original gasifier because when the engine was running at levels of power greater than 8.4 kWe, a sudden interruption occurred due to flooding of the gas cleaning water. Upon the required modifications, the gasifier was able to produce sufficient poor gas to generate 26 kWe of power. The engine was tested for different ignition advance angles: 22°, 20°, 16° e 9° and for two different types of wood. It was noted that the angle adjustment had a great influence not only over the engine performance itself, but also on the efficiencies of the gasifier and consequently of the system composed by the gasifier and the electrical generator. In this adjustment the ignition advance angle of 9° stood out as one that could guarantee economic advantages and better performance for the system, when the entire experimental range of power is considered. Taking into account that in our experiments an additional of 6 kWe was obtained as compared to the designed value for the Indian system operating with a dual engine, running with diesel and poor gas, we can conclude that the present results and considerations point to the importance of using a biomass gasifier as a successful means of solving the electrical energy dilemma in Brazil.